The Impact of Class III Obesity on Participation in the Occupations of Everyday Living for Adults Seeking Treatment for Obesity - Forhan, Mary (My University, 2009)
This thesis summarizes the findings of two studies, one qualitative and one quantitative, that examined the participation of adults with class III obesity in occupations of everyday living which included work, self-care, recreation and rest. The results of this research form the basis of the three manuscripts included in this thesis.
The purpose of the first study was to describe the experience of living with obesity in the context of participation in daily activities and to identify factors that constrain or facilitate participation. Using a descriptive, phenomenological approach, in-depth, semi-structured interviews were conducted with 10 adults who were enrolled in an obesity treatment program. This analysis revealed themes that underscored the tensions, barriers and coping strategies across and within occupations of everyday living. The quality and diversity of occupation was influenced by several barriers within their environment such as inaccessible physical spaces and negative attitudes towards persons with obesity. Participants described their lives as being "on-hold" until weight was lost. Findings from this study were used to develop a larger, cross sectional survey.
The purpose of the cross sectional survey (study number 2) was to describe how adults with class III obesity spend their daily time and to identify factors that predict participation in the occupations of everyday living. An analysis of data collected (n= 128) using the Occupational Questionnaire revealed that the distribution of time spent across activities classified as work, daily living, recreation and rest was similar to the time use of adults with chronic health conditions. A multiple regression analysis (n=140) resulted in a model in which factors including social support and disability status explained 35% of the variance in satisfaction with participation.
Results of these studies contributed to a better understanding of the daily experience of participation in the occupations of everyday living for adults with class III obesity and the factors that best predict satisfaction with participation.
Keywords: rehabilitation science, obesity, participation